Mars or Mercury redux: The geopolitics of bilateral trade agreements - Barry Eichengreen; Arnaud Mehl; Livia Chițu (European Central Bank (ECB), 2019)
We analyze the role of economic and security considerations in bilateral trade agreements. We use the pre-World War I period to test whether trade agreements are governed by pecuniary factors, such as distance and other frictions measured by gravity covariates, or by geopolitical factors. While there is support for both hypotheses, we find that defense pacts boost the probability of trade agreements by as much as 20 percentage points. Our estimates imply that were the U.S. to alienate its geopolitical allies, the likelihood and benefits of successful bilateral agreements would fall significantly. Trade creation from an agreement between the U.S. and E.U. countries would decline by about 0.6 percent of total U.S. exports.
Keywords: F13; N20; 330; international trade agreements; alliances; geopolitics